The belt and road initiative: A hybrid model of regionalism - Andreas Grimmel; Yuan Li (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2018)
Initiated under the Presidency of Xi Jinping in 2013, the Belt and Road Initiative (BRI) is still a young, yet a fast-developing and most ambitious regionalist project. Despite BRI's great potential to shape international trade and - more broadly - international relations amongst participating countries and beyond, scientific studies so far have largely neglected the question of how BRI goes together with contemporary approaches of regionalism and regional integration. This article argues that BRI constitutes a type of hybrid regionalism that seems to largely elude the old-new-regionalism divide and instead, it embraces elements of both traditions. In order to elucidate this double nature of the project, we will first discuss the idea of integration theory that has been developed in the context of the European integration process as well as such approaches that came up in the context of approaches of new regionalism. On this basis, and by referring to central elements of BRI as well as current developments in the framework of the project, we will shed light on the parallels and differences of BRI with "old" and "new" regionalism.
Keywords: 330; Belt and Road Initiative; New Silk Road; Old regionalism; New regionalism; Regional integration; China